Հայրենիքի գաղափարի կենսունակությունը Իրանի հայ գաղթօջախում՝ ըստ «Էջմիածին» ամսագրի - Մկրտչյան, Կարեն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
С момента своего создания в 1944 году религиоведческий и арменоведческий журнал «Эчмиадзин» опубликовал ценные статьи о деятельности армянской общины Ирана. На страницах журнала можно найти многочисленные публикации на разные темы. Среди них: визит делегации во главе с Местоблюститеем Католикоса Всех Армян архиепископом Геворгом Чорекчяном в Тегеран в 1944 году и встречи с армянской общиной Ирана, деятельность Армянской епархии Ирана, роль известных ирано-армянских деятелей в развитии связей между родиной и диаспоров, пожертвования иранских армян, направленные родине во время Второй мировой войны. Особое внимание уделяется вопросу организации репатриации и участия в ней иранских армян. Since its inception in 1944, “Etchmiadzin” religious and Armenological journal of the Mother See of Holy Etchmiadzin has published valuable articles on the activities of the Armenian community in Iran. On the pages of the magazine, there are many publications related to the presentation of such issues as: visit of the delegation of the Deputy Patriarch of All Armenians headed by Archbishop Gevork Chorekchyan to Tehran in 1944, and meetings with the Iranian-Armenian community; activities of the Armenian Diocese of Iran, including the role of prominent Iranian-Armenian figures in the context of Homeland-Diaspora ties, as well as donations of Iranian-Armenians to the homeland during World War II. Special attention is paid to the issue of organizing repatriation and the participation of Iranian Armenians in it.
Keywords: Իրան; «Էջմիածին» ամսագիր; Հայ գաղթօջախներ